Case Report: Three cases of suspected female genital schistosomiasis and precancerous lesions for cervical cancer in a highly endemic country—from clinical management to public health implications - Marchese, Valentina; Rakotomalala, Zoly; Kutz, Jean-Marc; Ratefiarisoa, Sonya; Rakotomalala, Rivo; Rasamoelina, Tahinamandranto; Rakotozandrindrainy, Raphael; Rausche, Pia; Gheit, Tarik; Hampl, Monika; May, Jürgen; Rakotoarivelo, Rivo Andry; et al. (Frontiers in Tropical Diseases, 2023)
Female genital schistosomiasis (FGS) is a chronic manifestation of schistosomiasis, usually caused by Schistosoma haematobium infection, which can be responsible for infertility, ectopic pregnancy, and abortion, and is associated with an increased prevalence of HIV infection. No screening programs are currently recommended for FGS. Colposcopy, the conventionally suggested diagnostic tool for FGS, is also considered a crucial screening tool for cervical cancer (CC). We performed an experimental screening via colposcopy for FGS at primary healthcare centers (PHCCs) in the Boeny region of Madagascar, allowing for the detection of patients with both FGS signs and HPV-related dysplasia (HPV-dy). All suspected FGS cases were treated with praziquantel on the day of colposcopy, and all images of suspected CC or HPV-dy were re-assessed by a gynecologist and, if needed, patients were then provided with additional colposcopy for histologic diagnosis and treatment. We describe three cases of FGS and HPV-related precancerous lesions detected during the project, discussing the state of art of the relationship between CC, FGS and HPV and the real-life challenges encountered in terms of both patient compliance and the diagnostic and treatment cascade. Despite the current diagnostic limitations, a screening for FGS via colposcopy may contribute to the early identification of CC or precancerous lesions. The addition of visual inspection with acetic acid (VIA) during colposcopy for FGS screening could improve its impact on CC screening. In addition, although there is limited evidence of the effectiveness of praziquantel in FGS, treatment should in any case be proposed for suspicious lesions, given its safety and ease of administration. The benefit of combined screening could be maximised by increasing the availability of good quality services and improve awareness of both diseases among women